Fasting and diurnal blood ketonemia and glycemia responses to a six-week, energy-controlled ketogenic diet, supplemented with racemic R/S-BHB salts - Buga, Alex; Kackley, Madison L.; Crabtree, Christopher D.; Bedell, Teryn N.; Robinson, Bradley T.; Stoner, Justen T.; Decker, Drew D.; Hyde, Parker N.; LaFountain, Rich A.; Brownlow, Milene L.; O'Connor, Annalouise; Krishnan, Deepa; et al. (Clinical nutrition ESPEN, 2023)
Single doses of exogenous ketone salts (KS) transiently increase circulating beta-hydroxybutyrate (BHB) (∼1 mM; 1–2 h) regardless of starting levels of ketosis; however, no studies have explored how sustained use of KS influences measures of ketonemia and glycemia. To determine the response to a hypocaloric, well-formulated ketogenic diet (KD), with and without the inclusion of two daily racemic KS doses (6 g R-BHB + 6 g S-BHB per serving) on 1) daily fasting capillary R-BHB and glucose (R-BHB/GLUfast), 2) bi-weekly 13 h diurnal BHB and glucose (R-BHB/GLUdiur), 3) three-hours post–KS ingestion kinetics (R-BHBKS), and 4) bi-weekly fasting plasma enantiomer-specific BHB (R/S-BHBplasma). Non-diabetic adults with overweight and obesity were randomized to receive a precisely measured hypocaloric KD (∼75 %en of maintenance) for six weeks, supplemented twice-daily with KS or placebo (PL). A non-randomized comparison group was provided an isonitrogenous/isoenergetic low-fat diet (LFD). All meals were provided to subjects. Capillary blood was collected daily to measure R-BHB/GLUfast and hourly for R-BHB/GLUdiur. Plasma was collected to measure R/S-BHBplasma, insulin, fasting glucose, and insulin resistance (HOMA-IR). Total AUC was calculated using the trapezoidal method. Mean R-BHBfast increased significantly during KD + PL (1.0 mM BHB), an effect enhanced 26% during KD + KS. GLUfast AUC was −6% lower during KD + KS versus LFD. Mean R-BHBdiur increased 40% in KD + KS versus KD + PL, whereas GLUdiur decreased 13% during both KDs versus LFD. R-BHBKS peaked (Δ: ∼1 mM) 1 h after the morning KS dose, but not following the afternoon dose. Both R/S-BHBplasma increased during KD independent of KS inclusion. R-BHBplasma was 50-times greater compared to S-BHBplasma, and the KS augmented S-BHBplasma 50% more than PL. Fasting insulin and HOMA-IR decreased after 14 days independent of diet. A hypocaloric KD was effective at reducing diurnal glucose compared to a LFD independent of weight loss, but twice-daily racemic KS ingestion during KD augmented ketonemia, both as R- and S-BHB, and decreased mean fasting glucose beyond a KD alone. The hypoglycemic effects of KD in combination with exogenous ketones merit further investigation.